High-performance aluminum alloy, preparation process and application of high-performance aluminum alloy in battery tray

Through specific chemical formula and coating technology, high-performance aluminum alloy coatings are formed using compounds such as 2-(3,4-dihydroxyphenyl)ethylamine, 2-chloro-3,4-epoxy-1-butene, etc. The layer solves the problem of insufficient performance of traditional aluminum alloy materials under high corrosion media and temperature changes, achieves excellent corrosion resistance and cold and heat alternating performance, and meets the needs of battery trays and other applications.

CN119144212AInactive Publication Date: 2024-12-17CIXI YIMEIJIA ALUMINUM CO LTD

Patent Information

Application Number
CN202411639366.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional aluminum alloy materials have insufficient performance in environments of highly corrosive media and severe temperature changes. Especially in key applications such as battery trays, corrosion resistance and cold and heat resistance need to be further improved, and existing improvement methods are usually accompanied by Increased costs and complicated processes.

Method used

Using specific chemical formulas and coating technology, through the synergistic action of compounds such as 2-(3,4-dihydroxyphenyl)ethylamine, 2-chloro-3,4-epoxy-1-butene, citric acid, etc. Functional coatings are prepared and ultrasonic mixing and ultraviolet curing technology are used to form a high-performance aluminum alloy material coating, which significantly improves the corrosion resistance and heat-resistant alternation performance of the material.

Benefits of technology

It significantly reduces the corrosion rate of the material in various corrosive media, extends the service life, improves the resistance to cold and heat alternation, reduces the risk of cracking and shedding of the coating, enhances the reliability of the material, and optimizes production. Process efficiency and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-performance aluminum alloy, a preparation technology and application of the high-performance aluminum alloy in a battery tray, and belongs to the technical field of aluminum alloys, the high-performance aluminum alloy is subjected to surface treatment through functional paint, the paint contains mica powder, hexagonal boron nitride and other high-performance filler and auxiliaries, and the excellent performance of a coating is ensured. And a uniform and compact protection layer is formed through an ultraviolet irradiation curing process. Compared with the prior art, the aluminum alloy material disclosed by the invention shows a relatively low average corrosion rate in acidic, neutral and alkaline corrosion media, is good in performance in a cold and hot alternating resistance test, is free of cracks and does not crack, and has a wide application prospect in the field of battery trays.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to a high-performance aluminum alloy, a preparation process and an application thereof in a battery tray. Background Art

[0002] With the rapid development of modern industry, the requirements for material performance are getting higher and higher, especially in the fields of aerospace, automobile manufacturing, electronic equipment, etc. Aluminum alloy has become an indispensable material in these fields due to its advantages such as light weight, high strength, good conductivity and corrosion resistance. However, the performance of traditional aluminum alloy materials in extreme environments is still limited, especially in terms of stability in highly corrosive media environments and reliability under drastic temperature changes.

[0003] In the preparation process of aluminum alloy, common methods include melting, casting, extrusion and heat treatment. These processes can produce aluminum alloy materials with certain strength and corrosion resistance, but in specific high-performance applications, the performance of these materials still needs to be further improved. For example, as an important part of new energy vehicles, battery trays require materials to have excellent corrosion resistance and resistance to cold and hot alternation to ensure the long-term stable operation of the battery.

[0004] At present, in order to improve the performance of aluminum alloys, researchers try to achieve this by adding rare earth elements, using special heat treatment processes or developing new surface coating technologies. Although these methods have improved the performance of aluminum alloys to a certain extent, they are often accompanied by increased costs, complex processes or environmental problems. Therefore, developing an economical and efficient method to prepare high-performance aluminum alloys, especially to improve performance in key applications such as battery trays, has become a research hotspot in this field.

[0005] Chinese invention patent CN118308619A discloses a corrosion-resistant aluminum alloy material and its preparation process. The aluminum alloy material includes the following chemical compositions in mass percentage: Si: 0.05~0.15%, Fe: 0.1~0.2%, Cu: 1.2~1.5%, Mn: 0.7~0.9%, Mg: 2.5~3.8%, Zn: 10.2~12.4%, Ti: 0.02~0.04%, Zr: 0.08~0.15%, Sc: 0.2~0.4%, and the balance is Al. The invention obtains aluminum alloy material through melting, refining, casting, heat treatment and other processes, and applies corrosion-resistant coating on its surface. After UV curing treatment, it not only improves the durability and anti-flaking of the coating; at the same time, it enhances the corrosion resistance of the material and effectively extends the service life of the aluminum alloy material. However, the corrosion resistance and resistance to cold and hot alternation of the corrosion-resistant aluminum alloy material prepared by the invention need to be improved. Summary of the invention

[0006] In response to the above problems, the present invention aims to provide a preparation process for high-performance aluminum alloy, which can significantly improve the corrosion resistance and resistance to hot and cold cycles while maintaining the light weight and high strength of the aluminum alloy, especially showing excellent performance in applications such as battery trays.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A preparation process of a high-performance aluminum alloy comprises the following steps, measured in parts by weight: 2-(3,4-dihydroxyphenyl)ethylamine, 2-chloro-3,4-epoxy-1-butene and tetrabutylammonium bromide are mixed, heated, sodium hydroxide is added, washed and dried to obtain a pretreated product; Mixing citric acid, the pre-treated product, triphenylphosphine and 4-methoxyresorcinol, heating, extracting and rotary evaporating to obtain a post-treated product; The post-treated product, ethyl acetate and polypyrrole are mixed to obtain a functional agent; Mixing ethanol, propylene glycol methyl ether, epoxy resin, defoamer, the functional agent, mica powder, hexagonal boron nitride, tris(2-aminoethyl)amine, and leveling agent to obtain a functional coating; The surface of the aluminum alloy material is coated with the functional coating.

[0008] Preferably, the preparation of a high performance aluminum alloy comprises the following steps, measured in parts by weight: Step 1, 2-4 parts of 2-(3,4-dihydroxyphenyl)ethylamine, 15-20 parts of 2-chloro-3,4-epoxy-1-butene and 0.05-0.1 parts of tetrabutylammonium bromide are mixed, and then heated at 70-90° C. for 1-3 hours, and then the mixture is cooled to 40-60° C. and 0.5-0.7 parts of sodium hydroxide are added, and the treatment is continued for 4-6 hours, and after washing and drying, a pretreated product is obtained; Step 2, 4 to 8 parts of citric acid are mixed with 3 to 5 parts of the pre-treated product prepared in step 1, and 0.03 to 0.05 parts of triphenylphosphine and 0.01 to 0.03 parts of 4-methoxyresorcin are added, and after treating at 80 to 100° C. for 5 to 15 hours, the temperature is lowered to 40 to 60° C. and 15 to 25 parts of phytic acid are added, and the treatment is continued for 10 to 20 hours, and a post-treated product is obtained by extraction and rotary evaporation process; Step 3, mixing 3 to 5 parts of the post-treated product prepared in step 2 with 3 to 5 parts of ethyl acetate and 1 to 3 parts of polypyrrole, and filtering, washing and drying to obtain a functional agent; Step 4, adding 10 to 20 parts of ethanol and 10 to 20 parts of propylene glycol methyl ether into a mixing device, stirring and mixing for 20 to 40 minutes, adding 25 to 35 parts of epoxy resin, and stirring for 1 to 3 hours, then adding 0.4 to 0.6 parts of defoamer and stirring and mixing for 0.5 to 2 hours, adding 4 to 6 parts of the functional agent prepared in step 3, 2 to 4 parts of mica powder, 1 to 3 parts of hexagonal boron nitride and 4 to 6 parts of tris (2-aminoethyl) amine, and 0.2 to 0.4 parts of leveling agent and ultrasonically mixing to obtain a functional coating; Step 5: grinding, polishing, cleaning and drying the surface of the aluminum alloy material, and then coating it with the functional coating prepared in step 4, and irradiating it with ultraviolet light to finally obtain a high-performance aluminum alloy product.

[0009] In step 4, ultrasonic mixing is performed for 0.5 to 2 hours, the ultrasonic frequency is 20 to 60 kHz, and the power is 200 to 400 W.

[0010] The coating thickness in step 5 is 100-400 μm.

[0011] In step 5, 310-400 nm ultraviolet rays are irradiated for 1-3 minutes, and the irradiation intensity is controlled at 15-25 mW / cm².

[0012] The leveling agent is one of BYK-3456 and BYK-332.

[0013] The defoamer is one of BYK-093 and BYK-024.

[0014] The preparation method of the aluminum alloy material is as follows, in parts by weight: S1. Dry 970-980 parts of aluminum block, 2-3 parts of iron, 0.5-2 parts of manganese and 0.5-2 parts of chromium powder, 8-10 parts of magnesium block, 0.5-0.7 parts of zinc block, 0.5-2 parts of titanium block, 2-3 parts of copper block, 5-6 parts of polysilicon, 0.05-0.2 parts of scandium powder, 0.3-0.5 parts of lanthanum block, 0.1-0.3 parts of cerium block and 0.2-0.4 parts of praseodymium block in a furnace at 200-350°C for 1-3 hours, then put the aluminum block into a smelting furnace and melt it at a temperature of 650-800°C. After the melting is completed, add polysilicon, iron, titanium block, manganese, chromium powder, zinc block, scandium powder, lanthanum block, cerium block and praseodymium block, continue to smelt, then add magnesium block and copper block, and after these materials are completely melted, stir for 5-15 minutes to obtain a uniform alloy melt; S2, introducing hexachloroethane gas into the alloy melt prepared in step S1 for refining treatment, with the gas flow rate set to 0.1-0.3 L / min, and the duration being 5-10 minutes. After the refining is completed, the mixture is allowed to stand for 5-10 minutes, and then slag is removed to obtain a refined aluminum alloy melt; S3, the refined aluminum alloy melt prepared in step S2 is made into an aluminum alloy ingot by gravity casting process, and the aluminum alloy ingot is then placed in a homogenization treatment device, and kept at 500-600° C. for 5-10 hours to complete the homogenization treatment, so as to obtain an aluminum alloy ingot after the homogenization treatment; S4, extruding the aluminum alloy ingot after homogenization treatment prepared in step S3 in an extruder, heating the aluminum alloy ingot to 500-600° C. during the extrusion process, maintaining a temperature gradient of 5-10° C., setting the extrusion barrel temperature to 430-480° C., the extrusion die temperature to 450-520° C., and controlling the extrusion speed to 4-6 m / min to obtain an alloy profile; S5, subjecting the alloy profile prepared in step S4 to an online solution quenching treatment, with the treatment temperature set at 500-550° C., and implementing three cooling methods of strong wind, spraying, and water through an online quenching device, and then performing an aging treatment to obtain an aluminum alloy in a T6 state; S6. Finally, the aluminum alloy in the T6 state is stretched and straightened to obtain an aluminum alloy material.

[0015] The stretching ratio of the stretching and straightening treatment in step S6 is 1-5%.

[0016] Application of the high performance aluminum alloy in a battery tray.

[0017] In the preparation process of the high performance aluminum alloy of the present invention, the functions of various substances are as follows: 2-(3,4-dihydroxyphenyl)ethylamine, as a polyhydroxy compound, reacts with epichlorohydrin in step 1 to help form a pretreatment with good bonding properties and chemical stability.

[0018] 2-Chloro-3,4-epoxy-1-butene is an epoxy compound, which reacts with 2-(3,4-dihydroxyphenyl)ethylamine in step 1 to participate in forming the chemical structure of the pretreatment, thereby providing a basis for subsequent coating performance.

[0019] Tetrabutylammonium bromide is used as a phase transfer catalyst, which promotes the reaction between 2-chloro-3,4-epoxy-1-butene and 2-(3,4-dihydroxyphenyl)ethylamine in step 1 and improves the reaction efficiency.

[0020] Sodium hydroxide acts as an alkaline substance in step 1 to promote the epoxy ring-opening reaction.

[0021] Citric acid is used as an organic acid in step 2. Its carboxyl group can form a chelate with the pre-treated material, which helps to stabilize the pre-treated material and prevent its side reactions. In addition, the acidic environment of citric acid can promote the progress of certain reactions.

[0022] Triphenylphosphine acts as a Lewis acid catalyst in step 2, which may promote the reaction of citric acid with the pretreatment material.

[0023] 4-Methoxyresorcinol may act as an antioxidant or stabilizer in step 2 to prevent oxidation during the reaction.

[0024] Phytic acid acts as a chelating agent in step 2, helping to stabilize metal ions and improve the corrosion resistance of the coating.

[0025] Ethyl acetate is used as a solvent in step 3 to dissolve the post-treatment product to facilitate mixing with polypyrrole.

[0026] Polypyrrole acts as a conductive polymer in step 3 to provide electrical conductivity and enhance the mechanical properties of the coating.

[0027] Epoxy resin is used as the main film-forming substance in step 4 to provide the basic structure and bonding properties of the coating.

[0028] Defoamer BYK-093 is used in step 4 to reduce bubbles generated during the coating mixing process and ensure uniform coating.

[0029] The leveling agent BYK-3456 is used in step 4 to improve the flow and surface smoothness of the coating.

[0030] Mica powder is used as a filler in step 4 to improve the mechanical strength and heat resistance of the coating.

[0031] Hexagonal boron nitride acts as a high-performance filler in step 4, providing thermal and chemical stability to the coating.

[0032] Tris(2-aminoethyl)amine may act as a curing agent in step 4 to promote crosslinking of the epoxy resin.

[0033] In the aluminum alloy material preparation method, the functions of various substances are as follows: Aluminum blocks, as the main component of aluminum alloys, provide the basic properties of alloys, such as light weight, good conductivity and corrosion resistance.

[0034] Iron, as one of the alloying elements, can improve the strength and hardness of aluminum alloy.

[0035] Manganese is often used to improve the strength and processing properties of alloys.

[0036] Chromium powder can increase the hardness and wear resistance of the alloy while enhancing corrosion resistance.

[0037] Magnesium blocks improve the strength and corrosion resistance of the alloy, while reducing density and increasing specific strength.

[0038] Zinc increases the alloy's strength and corrosion resistance.

[0039] Titanium blocks refine the grains and improve the strength and heat resistance of the alloy.

[0040] Copper blocks increase the alloy's strength and corrosion resistance.

[0041] Polysilicon acts as a reinforcing agent to improve the mechanical properties and wear resistance of the alloy.

[0042] Scandium powder is added as a trace element to improve the strength and heat resistance of the alloy.

[0043] Lanthanum, as a rare earth element, improves the physical properties of the alloy.

[0044] Cerium, as a rare earth element, improves the oxidation resistance and corrosion resistance of the alloy.

[0045] Praseodymium, as a rare earth element, improves the performance of the alloy.

[0046] Hexachloroethane gas is used to remove hydrogen and other impurities from the alloy during the refining process to improve the purity of the alloy.

[0047] Through the synergistic effect of these substances, the preparation process of the present invention can produce high-performance aluminum alloy materials with excellent properties, which are particularly suitable for applications requiring high corrosion resistance and resistance to alternating hot and cold temperatures, such as battery trays.

[0048] Compared with the prior art, it has the following beneficial effects: 1) By adopting a specific chemical formula and coating technology, the high-performance aluminum alloy of the present invention exhibits more excellent corrosion resistance, which significantly reduces the corrosion rate in various corrosive media, thereby extending the service life of the material.

[0049] 2) After being treated with the coating, the aluminum alloy material of the present invention exhibits better resistance to alternating hot and cold conditions and can remain stable even in harsh environments of alternating hot and cold conditions, thereby reducing the risk of cracking and falling off of the coating and improving the reliability of the material.

[0050] 3) The preparation process of the present invention is optimized in details, such as precise control of reaction conditions and material ratios, making the entire production process more efficient and environmentally friendly, while ensuring the consistency and quality of the product, meeting the specific requirements of high-performance aluminum alloy materials in applications such as battery trays. DETAILED DESCRIPTION

[0051] Main sources of substances: The weight average molecular weight of polypyrrole was 5,000.

[0052] Epoxy resin, model, NPEL-128, viscosity: 14000mPas.

[0053] Hexagonal boron nitride, particle size: 0.5~3.0μm.

[0054] Mica powder: particle size: 1250 mesh.

[0055] Leveling agent BYK-3456 and defoaming agent BYK-093 were purchased from BYK, Germany.

[0056] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0057] The design idea of ​​the present invention is to develop a high-performance aluminum alloy material and its application in battery trays through refined chemical synthesis processes and surface treatment technologies. This process prepares a functional coating with excellent corrosion resistance and resistance to hot and cold cycles through specific chemical reaction steps, which is then applied to the surface of the aluminum alloy to form a protective layer, thereby significantly improving the overall performance of the aluminum alloy. This process involves precisely controlled chemical synthesis, refined material processing, and advanced surface coating technology, ensuring the high performance of aluminum alloy materials in applications such as battery trays.

[0058] Example 1

[0059] A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 2-(3,4-dihydroxyphenyl)ethylamine, 18 kg of 2-chloro-3,4-epoxy-1-butene and 0.08 kg of tetrabutylammonium bromide were mixed, and then heated at 80° C. for 2 hours. Subsequently, the mixture was cooled to 50° C. and 0.6 kg of sodium hydroxide was added, and the treatment was continued for 5 hours. After washing and drying, a pretreated product was obtained; Step 2, 6 kg of citric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0060] The preparation method of the aluminum alloy material is as follows: S1. Dry 976kg of aluminum block, 2.5kg of iron, 1kg of manganese and 1kg of chromium powder, 9kg of magnesium block, 0.6kg of zinc block, 1kg of titanium block, 2.5kg of copper block, 5.4kg of polysilicon, 0.1kg of scandium powder, 0.4kg of lanthanum block, 0.2kg of cerium block and 0.3kg of praseodymium block in a furnace at 300°C for 2 hours, then put the aluminum block into a smelting furnace and melt it at a temperature of 700°C. After the melting is completed, add polysilicon, iron, titanium block, manganese, chromium powder, zinc block, scandium powder, lanthanum block, cerium block and praseodymium block, continue to smelt, then add magnesium block and copper block, and after these materials are completely melted, stir for 10 minutes to obtain a uniform alloy melt; S2, introducing hexachloroethane gas into the alloy melt prepared in step S1 for refining treatment, with the gas flow rate set to 0.2 L / min, and the duration being 8 minutes. After the refining is completed, the mixture is allowed to stand for 8 minutes, and then slag is removed to obtain a refined aluminum alloy melt; S3, the refined aluminum alloy melt prepared in step S2 is made into an aluminum alloy ingot by gravity casting process, and the aluminum alloy ingot is then placed in a homogenization treatment device and kept at 550° C. for 7 hours to complete the homogenization treatment, thereby obtaining an aluminum alloy ingot after homogenization treatment; S4, extruding the aluminum alloy ingot after homogenization treatment prepared in step S3 in an extruder, heating the aluminum alloy ingot to 550° C. during the extrusion process, maintaining a temperature gradient of 8° C., setting the extrusion barrel temperature to 450° C., the extrusion die temperature to 490° C., and controlling the extrusion speed to 5 m / min to obtain an alloy profile; S5, subjecting the alloy profile prepared in step S4 to an online solution quenching treatment, with the treatment temperature set at 530° C., and implementing three cooling methods of strong wind, spraying, and water through an online quenching device, and then performing an aging treatment to obtain an aluminum alloy in T6 state; S6. Finally, the aluminum alloy in the T6 state is stretched and straightened with a stretching ratio of 1.5% to obtain an aluminum alloy material.

[0061] Example 2

[0062] A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 1-naphthol is mixed with 18 kg of 2-chloro-3,4-epoxy-1-butene and 0.08 kg of tetrabutylammonium bromide, and then heated at 80° C. for 2 hours. Subsequently, the mixture is cooled to 50° C. and 0.6 kg of sodium hydroxide is added, and the treatment is continued for 5 hours. After washing and drying, a pretreated product is obtained; Step 2, 6 kg of citric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0063] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0064] Example 3

[0065] A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 1,5-dihydroxynaphthalene is mixed with 18 kg of 2-chloro-3,4-epoxy-1-butene and 0.08 kg of tetrabutylammonium bromide, and then heated at 80° C. for 2 hours. Subsequently, the mixture is cooled to 50° C. and 0.6 kg of sodium hydroxide is added, and the treatment is continued for 5 hours. After washing and drying, a pretreated product is obtained; Step 2, 6 kg of citric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0066] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0067] Example 4

[0068] A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 1-amino-8-naphthol-4-sulfonic acid is mixed with 18 kg of 2-chloro-3,4-epoxy-1-butene and 0.08 kg of tetrabutylammonium bromide, and then heated at 80° C. for 2 hours, then the mixture is cooled to 50° C. and 0.6 kg of sodium hydroxide is added, and the treatment is continued for 5 hours, and after washing and drying, a pretreated product is obtained; Step 2, 6 kg of citric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0069] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0070] Example 5

[0071] A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 2-(3,4-dihydroxyphenyl)ethylamine, 18 kg of 1,4-dichloro-2,3-butylene oxide and 0.08 kg of tetrabutylammonium bromide were mixed, and then heated at 80° C. for 2 hours. Subsequently, the mixture was cooled to 50° C. and 0.6 kg of sodium hydroxide was added, and the treatment was continued for 5 hours. After washing and drying, a pretreated product was obtained; Step 2, 6 kg of citric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0072] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0073] Example 6

[0074] A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 2-(3,4-dihydroxyphenyl)ethylamine, 18 kg of 2-chloro-3,4-epoxy-1-butene and 0.08 kg of tetrabutylammonium bromide were mixed, and then heated at 80° C. for 2 hours. Subsequently, the mixture was cooled to 50° C. and 0.6 kg of sodium hydroxide was added, and the treatment was continued for 5 hours. After washing and drying, a pretreated product was obtained; Step 2, 6 kg of L-tartaric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0075] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0076] Example 7

[0077] A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 2-(3,4-dihydroxyphenyl)ethylamine, 18 kg of 2-chloro-3,4-epoxy-1-butene and 0.08 kg of tetrabutylammonium bromide were mixed, and then heated at 80° C. for 2 hours. Subsequently, the mixture was cooled to 50° C. and 0.6 kg of sodium hydroxide was added, and the treatment was continued for 5 hours. After washing and drying, a pretreated product was obtained; Step 2, 6 kg of dihydroxytartaric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0078] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0079] Comparative Example 1 A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 4-allylcatechol, 18 kg of 2-chloro-3,4-epoxy-1-butene and 0.08 kg of tetrabutylammonium bromide were mixed, and then heated at 80° C. for 2 hours. Subsequently, the mixture was cooled to 50° C. and 0.6 kg of sodium hydroxide was added, and the treatment was continued for 5 hours. After washing and drying, a pretreated product was obtained; Step 2, 6 kg of citric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0080] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0081] Comparative Example 2 A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 2-(3,4-dihydroxyphenyl)ethylamine, 18 kg of epichlorohydrin and 0.08 kg of tetrabutylammonium bromide were mixed, and then heated at 80° C. for 2 hours. Subsequently, the mixture was cooled to 50° C. and 0.6 kg of sodium hydroxide was added, and the treatment was continued for 5 hours. After washing and drying, a pretreated product was obtained; Step 2, 6 kg of citric acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0082] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0083] Comparative Example 3 A preparation process of a high-performance aluminum alloy comprises the following steps: Step 1, 3 kg of 2-(3,4-dihydroxyphenyl)ethylamine, 18 kg of 2-chloro-3,4-epoxy-1-butene and 0.08 kg of tetrabutylammonium bromide were mixed, and then heated at 80° C. for 2 hours. Subsequently, the mixture was cooled to 50° C. and 0.6 kg of sodium hydroxide was added, and the treatment was continued for 5 hours. After washing and drying, a pretreated product was obtained; Step 2, 6 kg of lactic acid was mixed with 4 kg of the pre-treated product prepared in step 1, and 0.04 kg of triphenylphosphine and 0.02 kg of 4-methoxyresorcin were added. After treating at 90° C. for 10 hours, the temperature was lowered to 50° C. and 20 kg of phytic acid was added. The treatment was continued for 15 hours, and a post-treated product was obtained by extraction and rotary evaporation process; Step 3, 4 kg of the post-processed product prepared in step 2 is mixed with 4 kg of ethyl acetate and 2 kg of polypyrrole, and filtered, washed and dried to obtain a functional agent; Step 4, 15kg of ethanol and 15kg of propylene glycol methyl ether were put into a mixing device, stirred and mixed for 30 minutes, 30kg of epoxy resin was added, and stirring was continued for 2 hours, and 0.5kg of defoamer BYK-093 was added and stirred for 1 hour, and 5kg of the functional agent prepared in step 3, 3kg of mica powder, 2kg of hexagonal boron nitride and 5kg of tris(2-aminoethyl)amine, and 0.3kg of leveling agent BYK-3456 were added and ultrasonically mixed for 1 hour, with an ultrasonic frequency of 40kHz and a power of 300W to obtain a functional coating; Step 5: Grind, polish, clean and dry the surface of the aluminum alloy material, and then coat it with the functional coating prepared in step 4 with a coating thickness of 200 μm. Irradiate with 360 nm ultraviolet light for 2 minutes with an irradiation intensity controlled at 20 mW / cm² to finally obtain a high-performance aluminum alloy product.

[0084] The preparation method of the aluminum alloy material is the same as that in Example 1.

[0085] Comparative Example 4 A process for preparing an aluminum alloy material comprises the following steps: S1. Dry 976kg of aluminum block, 2.5kg of iron, 1kg of manganese and 1kg of chromium powder, 9kg of magnesium block, 0.6kg of zinc block, 1kg of titanium block, 2.5kg of copper block, 5.4kg of polysilicon, 0.1kg of scandium powder, 0.4kg of lanthanum block, 0.2kg of cerium block and 0.3kg of praseodymium block in a furnace at 300°C for 2 hours, then put the aluminum block into a smelting furnace and melt it at a temperature of 700°C. After the melting is completed, add polysilicon, iron, titanium block, manganese, chromium powder, zinc block, scandium powder, lanthanum block, cerium block and praseodymium block, continue to smelt, then add magnesium block and copper block, and after these materials are completely melted, stir for 10 minutes to obtain a uniform alloy melt; S2, introducing hexachloroethane gas into the alloy melt prepared in step S1 for refining treatment, with the gas flow rate set to 0.2 L / min, and the duration being 8 minutes. After the refining is completed, the mixture is allowed to stand for 8 minutes, and then slag is removed to obtain a refined aluminum alloy melt; S3, the refined aluminum alloy melt prepared in step S2 is made into an aluminum alloy ingot by gravity casting process, and the aluminum alloy ingot is then placed in a homogenization treatment device and kept at 550° C. for 7 hours to complete the homogenization treatment, thereby obtaining an aluminum alloy ingot after homogenization treatment; S4, extruding the aluminum alloy ingot after homogenization treatment prepared in step S3 in an extruder, heating the aluminum alloy ingot to 550° C. during the extrusion process, maintaining a temperature gradient of 8° C., setting the extrusion barrel temperature to 450° C., the extrusion die temperature to 490° C., and controlling the extrusion speed to 5 m / min to obtain an alloy profile; S5, subjecting the alloy profile prepared in step S4 to an online solution quenching treatment, with the treatment temperature set at 530° C., and implementing three cooling methods of strong wind, spraying, and water through an online quenching device, and then performing an aging treatment to obtain an aluminum alloy in T6 state; S6. Finally, the aluminum alloy in the T6 state is stretched and straightened with a stretching ratio of 1.5% to obtain an aluminum alloy material.

[0086] Test Example 1 Corrosion resistance test: 5% HCl solution (acidic), 3.5% NaCl solution (neutral), and 5% NaOH solution (alkaline) were selected as corrosive media, and the corrosion resistance of the high-performance aluminum alloys and aluminum alloy materials prepared in the embodiments of the present invention and the comparative examples was tested by static immersion experiments. The average corrosion rates of the high-performance aluminum alloys and aluminum alloy materials in different corrosive media were calculated according to the following formula.

[0087] V=(m1-m2) / St In the above formula: V is the average corrosion rate of high-performance aluminum alloy, mg·mm -2 ·h -1 ; m1 is the mass of the magnet before the experiment, mg; m2 is the mass of the magnet after cleaning the corrosion products and drying, mg; S is the surface area of ​​the magnet, mm 2 ; t is the soaking time, h; The test results are shown in Table 1.

[0088] Table 1

[0089] Test Example 2 Hot and cold alternating performance test: The high-performance aluminum alloy prepared in the embodiment of the present invention and the comparative example is placed in a muffle furnace, heated to 100°C, kept warm for 5 hours, taken out, and soaked in cold water for 1 hour, which is one cycle. Repeat 20 cycles and observe the changes in the paint film. If there is no peeling or cracking of the paint film, it means that the paint film has good hot and cold alternating performance.

[0090] The test results are shown in Table 2.

[0091] Table 2

[0092] It can be seen from the data in Tables 1 and 2 that the high-performance aluminum alloy prepared in Example 1 has the best corrosion resistance and does not crack or split after being subjected to alternating hot and cold conditions.

[0093] In Example 1, the unique molecular structure and chemical properties of 2-(3,4-dihydroxyphenyl)ethylamine enable it to exhibit excellent corrosion resistance and resistance to hot and cold alternation in the coating. Its two hydroxyl groups and one amino group enhance the molecular stability through hydrogen bonds, while improving the adhesion to the metal surface. The benzene ring structure provides high temperature stability for the coating, allowing it to remain firm in a hot and cold alternating environment. The presence of amino groups increases the reactivity of the molecule and can form stable chemical bonds with other components, thereby further improving the corrosion resistance and overall performance of the coating. The introduction of 2-chloro-3,4-epoxy-1-butene also further enhances the protective effect of the coating. Compared with epichlorohydrin, 1,4-dichloro-2,3-epoxybutane, etc. used in other embodiments, the molecular structure of 2-chloro-3,4-epoxy-1-butene gives higher chemical stability and adhesion, and can be more firmly bonded to the metal surface. The compound has strong reaction activity, good film-forming properties, and helps to form a dense and uniform coating structure, thereby improving corrosion resistance and resistance to hot and cold alternation. During the coating preparation process, citric acid, as an organic acid, further improves the coating performance through its unique molecular structure. Multiple carboxyl groups in the citric acid molecule can form a chelate structure with the metal surface, effectively enhancing the stability and corrosion resistance of the coating. At the same time, the acidic environment of citric acid helps to promote certain reactions, especially in epoxy resin curing, which can improve the adhesion and uniformity of the coating. Citric acid also synergizes with the pretreatment through chelation and catalysis to inhibit the occurrence of side reactions, thereby enhancing the overall stability of the coating. In summary, the synergistic effect of 2-(3,4-dihydroxyphenyl)ethylamine, 2-chloro-3,4-epoxy-1-butene and citric acid in the coating forms a dense chemical structure, which gives the coating excellent corrosion resistance, heat resistance and mechanical properties, and can meet the use requirements of high-performance aluminum alloy products in complex environments.

Claims

1. A preparation process for high performance aluminum alloy, It is characterized in that The method comprises the following steps, in parts by weight: 2-(3,4-dihydroxyphenyl)ethylamine, 2-chloro-3,4-epoxy-1-butene and tetrabutylammonium bromide are mixed, heated, sodium hydroxide is added, washed and dried to obtain a pretreated product; Mixing citric acid, the pre-treated product, triphenylphosphine and 4-methoxyresorcinol, heating, extracting and rotary evaporating to obtain a post-treated product; The post-treated product, ethyl acetate and polypyrrole are mixed to obtain a functional agent; Mixing ethanol, propylene glycol methyl ether, epoxy resin, defoamer, the functional agent, mica powder, hexagonal boron nitride, tris(2-aminoethyl)amine, and leveling agent to obtain a functional coating; The surface of the aluminum alloy material is coated with the functional coating.

2. The process for preparing the high performance aluminum alloy according to claim 1, It is characterized in that The method comprises the following steps, in parts by weight: Step 1, 2-4 parts of 2-(3,4-dihydroxyphenyl)ethylamine, 15-20 parts of 2-chloro-3,4-epoxy-1-butene and 0.05-0.1 parts of tetrabutylammonium bromide are mixed, and then heated at 70-90° C. for 1-3 hours, and then the mixture is cooled to 40-60° C. and 0.5-0.7 parts of sodium hydroxide are added, and the treatment is continued for 4-6 hours, and after washing and drying, a pretreated product is obtained; Step 2, 4 to 8 parts of citric acid are mixed with 3 to 5 parts of the pre-treated product prepared in step 1, and 0.03 to 0.05 parts of triphenylphosphine and 0.01 to 0.03 parts of 4-methoxyresorcin are added, and after treating at 80 to 100° C. for 5 to 15 hours, the temperature is lowered to 40 to 60° C. and 15 to 25 parts of phytic acid are added, and the treatment is continued for 10 to 20 hours, and a post-treated product is obtained by extraction and rotary evaporation process; Step 3, mixing 3 to 5 parts of the post-treated product prepared in step 2 with 3 to 5 parts of ethyl acetate and 1 to 3 parts of polypyrrole, and filtering, washing and drying to obtain a functional agent; Step 4, adding 10 to 20 parts of ethanol and 10 to 20 parts of propylene glycol methyl ether into a mixing device, stirring and mixing for 20 to 40 minutes, adding 25 to 35 parts of epoxy resin, and stirring for 1 to 3 hours, then adding 0.4 to 0.6 parts of defoamer and stirring and mixing for 0.5 to 2 hours, adding 4 to 6 parts of the functional agent prepared in step 3, 2 to 4 parts of mica powder, 1 to 3 parts of hexagonal boron nitride and 4 to 6 parts of tris (2-aminoethyl) amine, and 0.2 to 0.4 parts of leveling agent and ultrasonically mixing to obtain a functional coating; Step 5: The functional coating is coated on the surface of the aluminum alloy material, and then irradiated with ultraviolet light to obtain a high-performance aluminum alloy.

3. The preparation process of the high performance aluminum alloy according to claim 2, It is characterized in that In step 4, ultrasonic mixing is performed for 0.5 to 2 hours, the ultrasonic frequency is 20 to 60 kHz, and the power is 200 to 400 W.

4. The process for preparing the high performance aluminum alloy according to claim 2, It is characterized in that In step 4, the leveling agent is one of BYK-3456 and BYK-332; and the defoaming agent is one of BYK-093 and BYK-024.

5. The process for preparing the high performance aluminum alloy according to claim 2, It is characterized in that The coating thickness in step 5 is 100-400 μm.

6. The process for preparing the high performance aluminum alloy according to claim 2, It is characterized in that In step 5, 310-400 nm ultraviolet rays are irradiated for 1-3 minutes, and the irradiation intensity is controlled at 15-25 mW / cm².

7. The process for preparing the high performance aluminum alloy according to claim 1, It is characterized in that The preparation method of the aluminum alloy material is as follows, in parts by weight: S1. Dry 970-980 parts of aluminum block, 2-3 parts of iron, 0.5-2 parts of manganese and 0.5-2 parts of chromium powder, 8-10 parts of magnesium block, 0.5-0.7 parts of zinc block, 0.5-2 parts of titanium block, 2-3 parts of copper block, 5-6 parts of polysilicon, 0.05-0.2 parts of scandium powder, 0.3-0.5 parts of lanthanum block, 0.1-0.3 parts of cerium block and 0.2-0.4 parts of praseodymium block in a furnace at 200-350°C for 1-3 hours, then put the aluminum block into a smelting furnace and melt it at a temperature of 650-800°C. After the melting is completed, add polysilicon, iron, titanium block, manganese, chromium powder, zinc block, scandium powder, lanthanum block, cerium block and praseodymium block, continue to smelt, then add magnesium block and copper block, and after these materials are completely melted, stir for 5-15 minutes to obtain a uniform alloy melt; S2, introducing hexachloroethane gas into the alloy melt prepared in step S1 for refining treatment, with the gas flow rate set to 0.1-0.3 L / min, and the duration being 5-10 minutes. After the refining is completed, the mixture is allowed to stand for 5-10 minutes, and then slag is removed to obtain a refined aluminum alloy melt; S3, the refined aluminum alloy melt prepared in step S2 is made into an aluminum alloy ingot by gravity casting process, and the aluminum alloy ingot is then placed in a homogenization treatment device, and kept at 500-600° C. for 5-10 hours to complete the homogenization treatment, so as to obtain an aluminum alloy ingot after the homogenization treatment; S4, extruding the aluminum alloy ingot after homogenization treatment prepared in step S3 in an extruder, heating the aluminum alloy ingot to 500-600° C. during the extrusion process, maintaining a temperature gradient of 5-10° C., setting the extrusion barrel temperature to 430-480° C., the extrusion die temperature to 450-520° C., and controlling the extrusion speed to 4-6 m / min to obtain an alloy profile; S5, subjecting the alloy profile prepared in step S4 to an online solution quenching treatment, with the treatment temperature set at 500-550° C., and implementing three cooling methods of strong wind, spraying, and water through an online quenching device, and then performing an aging treatment to obtain an aluminum alloy in a T6 state; S6. Finally, the aluminum alloy in the T6 state is stretched and straightened to obtain an aluminum alloy material.

8. The process for preparing the high performance aluminum alloy according to claim 7, It is characterized in that The stretching ratio of the stretching and straightening treatment in step S6 is 1-5%.

9. A high performance aluminum alloy, It is characterized in that Prepared by the preparation process described in any one of claims 1 to 8.

10. A use of the high performance aluminum alloy as claimed in claim 9, It is characterized in that The high performance aluminum alloy is used in a battery tray.

Citation Information

Patent Citations

  • High-strength high-toughness corrosion-resistant aluminum alloy sectional material

    CN105420567A

  • Wear-resistant aluminum alloy section and preparation method thereof

    CN106752713A

  • Biology base citric acid epoxy resin composition as well as curing method and application thereof

    CN109517341A

  • Processing method of corrosion-resistant aluminum plate

    CN113073216A

  • Production method of corrosion-resistant aluminum alloy profile for ships

    CN116179053A

Cited By

  • High-strength alloy material based on rail transit vehicle and processing technology of high-strength alloy material

    CN119491123A